2021
DOI: 10.35490/ec3.2021.159
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Material Passport Ontology to Enable Circularity for Industrialized Construction

Abstract: There is a need to collect, store, and share product data to enable circularity in industrialized construction supply chains. To do this, the concept of a Material Passport (MP) has been proposed, but exactly how MPs should be created and managed is less understood, especially in consideration of industrialized construction product platforms. This paper proposes a knowledge and process representation framework called the Material Passport Ontology (MPO). The MPO outlines key components of MPs and their interre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As stated, most of the work on material passports in the construction sector focused on developing material passports at a building level Heisel and Rau-Oberhuber, 2020;Kedir, Bucher, and Hall, 2021). However, from a circular perspective, the material passport should have additional information to support city-level activities such as urban planning (Herthogs et al, 2012;Li, Quan, and Yang, 2016).…”
Section: Materials Passportsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated, most of the work on material passports in the construction sector focused on developing material passports at a building level Heisel and Rau-Oberhuber, 2020;Kedir, Bucher, and Hall, 2021). However, from a circular perspective, the material passport should have additional information to support city-level activities such as urban planning (Herthogs et al, 2012;Li, Quan, and Yang, 2016).…”
Section: Materials Passportsmentioning
confidence: 99%
“…Further linked-data technologies have also been used in the city scale for decision-making during city planning (Chadzynski et al, 2021;. Also, ontologies have been used to develop material passports to enable circular information flow in Industrialized construction (Kedir, Bucher, and Hall, 2021).…”
Section: Point Of Departurementioning
confidence: 99%
“…This shift can be achieved through improvements to develop better circular information flow (CIF). CIF refers to the development, management, and exchange of CE-relevant data [7] throughout the lifecycle of an asset in the built environment.…”
mentioning
confidence: 99%
“…The traditional construction industry is not currently equipped for the transition. That being said, approaches such as modularity in construction and industrial practices have been found to help promote the transition [7,10,11,12]. Industrialized Construction (IC), referring in this case to concepts such as modular building, prefabrication, robotics, and off-site manufacturing, offers tremendous opportunities for reducing environmental impact [7,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation